SUMBANGAN KOORDINASI MATA-TANGAN, POWER LENGAN, DAN POWER TUNGKAI TERHADAP FOREHAND DRIVE (Department of Sports Science, Faculty of Sports Science, Universitas Negeri Semarang)
Penelitian ini bertujuan untuk mengetahui sumbangan relatif dan sumbangan efektif koordinasi mata tangan, power otot lengan dan power otot tungkai terhadap hasil pukulan forehand drive pada atlet klub tenis lapangan Grose kota Semarang tahun 2012. Metode penelitian dengan survei tes. Diperoleh hasil sumbangan efektif koordinasi mata-tangan terhadap hasil pukulan forehand drive pada atlet klub tenis lapangan Grose kota Semarang yaitu sebesar 22,7 %, power otot lengan terhadap hasil pukulan forehand drive sebesar 17,9 %, power otot tungkai terhadap hasil pukulan forehand drive sebesar 33,9 %, Koordinasi mata-tangan, power otot lengan dan power otot tungkai secara bersama-sama memberikan sumbangan terhadap hasil pukulan forehand drive pada atlet tenis lapangan Grose kota Semarang yaitu sebesar 74,4 %.Penelitian dapat disimpulkan bahwa Koordinasi mata-tangan memberikan sumbangan yang kecil terhadap hasil pukulan forehand drive,power otot lengan memberikan sumbangan yang kecil terhadap hasil pukulan forehand drive, power otot tungkai memberikan sumbangan yang kecil terhadap hasil pukulan forehand drive, koordinasi mata-tangan, power otot lengan dan power otot tungkai secara bersama-sama memberikan sumbangan yang besar terhadap hasil pukulan forehand drive. The purpose of this study is to know how relative contribution and effective contribution for hand-eye coherency, arm muscle power, and leg muscle power according to forehand drive hit power result for Grose tennis court club Semarang athlete’s in 2012. The methode of this study is survey test. The datas is obtained from experimental test and measurement test with multiple regression test analytic methode. And the result of the test shows that effective contribution of hand-eye coherency according to forehand drive hit power result for Grose tennis court club Semarang athlete’s is 22,7%, arm muscle power according to forehand drive hit power result is 17,9%, and leg muscle power according to forehand drive hit power result is 33,9% and contribution for hand-eye coherency, arm muscle power, and leg muscle power in one relation according to forehand drive hit power result is 74,4%. From the analytics i can conclude that hand-eye coherency give a small impact according to forehand drive hit power result, arm muscle power give a small impact according to forehand drive hit power result, and leg muscle power give a small impact according to forehand drive hit power result. when hand-eye coherency, arm muscle power, and leg muscle power used all together, they can gave a big impact for forehand drive hit power result.